Inclusive education from a very beginning: Yerevan school N 20 principal’s narrative - Khosrovyan, Anahit
There are more than one billion “disabled persons” worldwide, 10% of whom are children mostly living in developing countries. Within the United Nations (UN) the term “disability” is defined as “any restriction or lack (resulting from an impairment) of ability to perform an activity in the way or within the range considered normal for a human being”. The UN and the United Nations Children’s Fund (UNICEF) endeavour for all children to have equitable access to education as a basic human right. Education is critical for children to develop their human capital and enhance their upcoming economic and social prospects. The “Salamanca Statement” adopted at the “World Conference on Special Educational Needs: Access and Quality” called upon all governments and urged them to: adopt as a matter of law or policy the principles of inclusive education, enrolling all children in regular schools, unless there are compelling reasons for doing otherwise. In developing countries understanding of inclusive education is closely related to the special education needs of students and their participation in regular school classes. From this perspective, this paper aims to tell a story of one school in Yerevan, the capital of Armenia from the very beginning till nowadays.
Keywords: Education